Assessing Vulnerability to Chronic Undernutrition among Under-Five Children in Egypt: Contextual Determinants of an Individual Consequence. (12th April 2012) - Mazumdar, Sumit
Abstract : Nutritional outcomes remain an important development indicator and reflect a household's vulnerability to improved quality of life. Drawing upon recent household survey data from Egypt, this paper applies hierarchical models to test the effect of contextual factors on chronic undernutrition among under-five children and identifies the demographic and socioeconomic characteristics that underscore such vulnerability. Results indicate considerable neighborhood effects influencing a household's nutritional choices. However, no significant effect could be identified for mother's education and women's decision-making power, but a clear positive association is evident between nutritional status and better health service utilization as well as child care and feeding practices. Focused intervention strategies need to augment household level behavioral change for these identified factors and supplement such individual efforts with targeted strategies aimed at vulnerable Egyptian communities to reduce child undernutrition.